ANALISIS KEUNTUNGAN PEDAGANG PENGECER DAGING SAPI DI PASAR TRADISIONAL KOTA MANADO - Butarbutar, Nicolas; Rorimpandey, B.; Legrans, R. A.J; Lumenta, I. D.R (Universitas Sam Ratulangi, 2014)
ABSTRACTBENEFIT ANALYSIS OF RETAIL TRADERS AT BEEF TRADITIONAL MARKET IN MANADO. The experiment was conducted at beef traditional market in Manado, particularly at â€œBersehati Jengki market regionâ€ and â€œPinasungkulan Ranotana market regionâ€. The problem in this study is how much the operating costs retailers spent in beef marketing activity and how much the benefit of beef marketing activity received by retailers when compared with the bank interest rate level. The purpose of the study was to find out the operating cost spent by retailers compared with the benefit in beef marketing activity in Manado traditional markets. Sources of data in this study were found from the primary and secondary data. The samples were taken using purposive sampling method. Data analysis model in this study were conducting by descriptive analysis approach and mathematical analysis aswell as the concept of profitability. The results of the study showed that the average operating costs used by retailers in beef marketing were Rp 60,000,258 per week or Rp 239,990,725 per month. The average amount of the benefits received by retailers in beef marketing were Rp14,822,681 per week or Rp 3,703,093 per month. Enterprises of beef retailers in Manado traditional markets were able to gain the benefit. This business is also able to achieve the better overall profitability value compared with the bank rate prevailing in Indonesia. The average value of profitability of beef retailers was 7.01% per month (84.16% per year) while the bank rate of Indonesia (SBBI) was 7.5%.Keywords: Profit, Retailers, Beef, Traditional Market, Manado